Novel fluorosilicone thermoplastic vulcanizates prepared via core‐shell dynamic vulcanization: Effect of fluororubber/silicone rubber ratio on morphology, crystallization behavior, and mechanical properties. (6th February 2018) - Chen, Yukun; Gong, Zhou; Cao, Liming; Wang, Youhong; Yuan, Daosheng; Xu, Chuanhui
Abstract : Recently, we have reported a novel core‐shell dynamic vulcanization method to prepare poly(vinylidene fluoride) (PVDF)/fluororubber (FKM)/silicone rubber (SR) thermoplastic vulcanizates (TPVs) with cross‐linked rubber core‐shell particles. However, the shell thickness on the properties has not been studied in detail. Herein, these PVDF‐based TPVs different FKM‐shell thickness were prepared by changing FKM/SR ratios. The effect of FKM‐shell/SR‐core ratio on morphology, crystallization, and mechanical properties of the ternary TPVs was studied. The results showed that the FKM shell had more positive effect on interfacial‐induced crystallization behavior than the SR core due to its better compatibility with PVDF. When the FKM/SR ratio was <1, FKM was not enough to encapsulate SR completely, which resulted in the formation of imperfect core‐shell structure. However, when the FKM/SR ratio was >1, perfect core‐shell structure was formed. Therefore, the mechanical properties improved with increasing FKM content; especially, a remarkable improvement was observed when FKM/SR ratio was >1. This study could provide more information for the design of TPVs with core‐shell structure.